2006
DOI: 10.1021/cm061011f
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescent Polyhedral Oligomeric Silsesquioxane-Based Nanoparticle

Abstract: A polyhedral oligomeric silsesquioxane (POSS)-based blue light electroluminescent nanoparticle, POSS-FL3, which contains a terfluorene chromophore on each of its eight arms, was easily prepared via the hydrosilation reaction between octakis(dimethylsiloxy)silsesquioxane and an allyl-functionalized terfluorene chromophore that emits blue light as a result of photo- or electroexcitation. POSS-FL3 exhibits good solubility in common organic solvents, such as chloroform, THF, toluene, p-xylene, and chlorobenzene, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 42 publications
0
28
1
2
Order By: Relevance
“…The performance of diodes using the POSS-(DPOC 10 -PPV) is obviously improved as compared to devices using the pristine polymer. Previous investigations of POSS based diodes have suggested the improvement of the light emission would be due to the fact that POSS units separate the polymer chains, and reducing aggregation effects [31][32][33]. However, such a process would imply a blue shift of the PL spectrum in POSS-polymer hybrid material, which is not observed in our samples.…”
Section: Device Characterizationcontrasting
confidence: 52%
“…The performance of diodes using the POSS-(DPOC 10 -PPV) is obviously improved as compared to devices using the pristine polymer. Previous investigations of POSS based diodes have suggested the improvement of the light emission would be due to the fact that POSS units separate the polymer chains, and reducing aggregation effects [31][32][33]. However, such a process would imply a blue shift of the PL spectrum in POSS-polymer hybrid material, which is not observed in our samples.…”
Section: Device Characterizationcontrasting
confidence: 52%
“…Tetrahydrofuran was distilled over sodium and benzophenone. Samples of 4,4‐difluoro‐1,3,5,7,8‐pentamethyl‐2,4‐diethyl‐4‐bora‐3a,4a‐diaza‐s‐indacene ( 1 ),52 1‐ethynyl‐8‐propargylicalcoholpyrene ( 3 ),53 3‐ethynylperylene ( 4 ),54 and 2‐bromo‐9,9‐di‐ n ‐butyl‐9H‐fluorene ( 5 ),55 were prepared and purified according to literature procedures. All reactions were carried out under argon using Schlenk‐tube and vacuum‐line techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, many literatures reported that the bulky organic and inorganic hybrid POSS nanoparticles could effectively reduce the aggregations of photoluminescence units in the active layers of organic molecule and polymer light-emitting diode devices (OLED [11][12][13][14][15][16] and PLED [17][18][19][20][21][22]). Furthermore, POSS molecules can be regarded as core-shell colloids with solvated alkyl or aryl shells to disperse insoluble siloxane cores in solution [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%